Etiological serotype and genotype distributions and clinical characteristics of group B streptococcus-inducing invasive disease among infants in South China - Yao Zhu; Jiayin Wu; Xinyi Zheng; Dengli Liu; Liping Xu; Dongmei Chen; Wenying Qiu; Zhongling Huang; Ronghua Zhong; Ling Chen; Mingyuan He; Simin Ma; et al. (BMC Pediatrics, 2020)
Abstract Background Group B streptococcus (GBS)-induced invasive disease is a major cause of illness and death among infants aged under 90 days in China; however, invasive GBS infection remains unknown in China. We aimed to describe the serotype and genotype distributions of early-onset disease (EOD) and late-onset disease (LOD), and to show the clinical correlations among various GBS serotypes and genotypes obtained from infants with invasive GBS infections. Methods Between June 1, 2016 and June 1, 2018, 84 GBS strains were collected from patients younger than 90 days at seven Chinese hospitals. Clinical data were retrospectively reviewed. GBS serotyping was conducted and multi-locus sequence typing was performed. Results Serotypes Ia, Ib, II, III, and V were detected. Serotype III (60.71%) was the most common, followed by Ia (16.67%) and Ib (14.29%). Intrapartum temperature ≥ 37.5 °C, chorioamnionitis, and mortality were noted in 28.57, 42.86, and 28.57% of patients with serotype Ia, respectively, and these rates were higher than those in patients with serotypes Ib and III (P = 0.041, P = 0.031, and P = 0.023, respectively). The incidence of respiratory distress was lower (P = 0.039) while that of purulent meningitis was higher (P = 0.026) in the serotype III group. Eighteen sequence types were detected among isolates, and ST17 [42.86% (36/84)] was the most prevalent. Conclusions GBS isolates belonging to serotypes Ia, Ib, and III are common in southern mainland China, and ST17 is highly prevalent. Differences were found in the clinical manifestations of invasive GBS disease induced by serotypes Ia and III.